2002
DOI: 10.1677/joe.0.1750033
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear effects: unexpected intracellular actions of insulin-like growth factor binding protein-3

Abstract: Insulin-like growth factor (IGF) binding protein (IGFBP)-3 has been shown to be a growth inhibitory, apoptosis-inducing molecule by virtue of its ability to bind IGFs, in addition to previously demonstrated IGFindependent effects. The recent discovery of the interaction between nuclear IGFBP-3 and 9-cis retinoic acid receptor-(retinoid X receptor RXR ), a nuclear receptor, and its involvement in the regulation of transcriptional signaling and apoptosis represents an important paradigm shift in the understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…The in vivo data presented here complements a compendium of in vitro data in prostate cancer models, showing that IGFBP-3 induces apoptosis, in a manner that could be unrelated to its IGF binding (24,25); and that it mediates many tumorsuppressive effects of cytokines and hormones (26). IGFBP-3 is secreted and reuptaken rapidly to the nucleus via distinct endocytic pathways (7) and nuclear localization is mediated by importin-h pathway via a bipartite basic consensus sequence near its COOH terminus (27,28).…”
Section: Discussionsupporting
confidence: 53%
“…The in vivo data presented here complements a compendium of in vitro data in prostate cancer models, showing that IGFBP-3 induces apoptosis, in a manner that could be unrelated to its IGF binding (24,25); and that it mediates many tumorsuppressive effects of cytokines and hormones (26). IGFBP-3 is secreted and reuptaken rapidly to the nucleus via distinct endocytic pathways (7) and nuclear localization is mediated by importin-h pathway via a bipartite basic consensus sequence near its COOH terminus (27,28).…”
Section: Discussionsupporting
confidence: 53%
“…We found that mainly nuclear IGFBP-3 was targeted by ubiquitin/proteasome-dependent destruction; however, polyubiquitination was very low for IGFBP-3 expressed in the lumen of the membranous organelles. These findings suggest that ubiquitin/proteasome-dependent destruction of nuclear IGFBP-3 may play an important role for the control of cell proliferation and apoptosis by IGFBP-3 (36).…”
Section: Discussionmentioning
confidence: 81%
“…In addition to IGF-1-and IGF-1R-dependent effects, recent reports have shown that IGFBP-3 may also act through distinct receptors and through nuclear translocation (14,15,20,21,29). Such IGF-1-and IGF-1R-independent mechanisms may play a role in the IGFBP-3 induction of apoptosis in Ewing cells, since in the absence of serum, wild-type IGFBP-3 is still able to trigger apoptosis, whereas a noninternalizable version of IGFBP-3 with a mutated NLS is inefficient.…”
Section: Discussionmentioning
confidence: 99%